Influence of façade orientation, floor height, substrate pH, and microbial inoculation on woody plants’ performance in vegetated façades in Southern Finland - Shu, Xi; Xie, Long; Kotze, D. Johan; Jauni, Miia; Lettojärvi, Iiris; Suonio, Taina H.; Nagase, Ayako; Lehvävirta, Susanna (Elsevier, 2024)
Urban densification has led to the adoption of vegetated façades as a nature-based strategy to increase urban green spaces and enhance urban living conditions. However, limited knowledge regarding suitable plants for vegetated façades can impede the process. In this field experiment conducted in Southern Finland, we investigated the performance of 12 potential plant taxa for a vegetated façade by assessing their visual appearance and sizes in relation to façade orientation, floor height, substrate pH, and mycorrhizal inoculation. The 12 plant taxa were categorized into 4 growth forms according to their morphologies: spreading conifers, dwarf conifers, creeping conifers, and climbers. We aimed to evaluate plant performance during the initial two growing seasons, which is critical for the successful establishment of these plants in vegetated façades. Eight of the twelve plant taxa exhibited relatively high performance in terms of visual appearance and size. Notably, creeping conifers outperformed other growth forms in visual appearance, which was most likely due to their close-to-ground morphology. Façade orientation and substrate pH were the most influential predictor variables. Façade orientation affected both plant visual appearance and size, while substrate pH primarily affected plant visual appearance. The east-facing façade (less exposure to sun and wind) and mildly acid substrate (pH 6–6.5) were more conducive to most of the plant taxa. Certain species and cultivars, such as Juniperus communis ‘Lalli’, maintained constant plant visual appearance and size regardless of façade orientation and substrate pH, suggesting their adaptability and stability across various conditions. Floor height and mycorrhizal inoculation only displayed marginal and taxon-specific impacts. Given that some plants in our vegetated façade exhibited optimal performance different from those in their reported natural habitats, we encourage conducting long-term, on-site experiments to identify suitable plants for vegetated façades to ensure successful vegetated façade implementation.
Keywords: adaptive planning; plant growth forms; plant size; plant visual assessment; urban green infrastructure; vertical greenery system